Optimalisasi Inovasi Wakaf Di Indonesia Era Digital Dalam Menjawab Tantangan Dan Peluang - Choirunnisak; Azka Amalia Jihad; Choirunnisak, Choirunnisak (Jurnal I-Philanthropy, 2024)
ABSTRACThe potential of waqf in Indonesia is immense, yet its realization remains far from optimal. This study discusses the optimization of waqf innovation in the digital era to support sustainable development in Indonesia. Through a qualitative approach and literature review, this research examines the challenges in optimizing waqf innovation in the digital era, the development of waqf innovation, and what can be done to enhance its optimization. The findings reveal several challenges, such as low digital literacy, limited public trust, and the lack of regulations supporting digital waqf innovation. The study also explores digitalization opportunities, including the use of technologies such as crowdfunding, blockchain, and smart waqf applications, which can improve efficiency, transparency, and accessibility in waqf management. With collaboration among the government, waqf institutions, the private sector, academics, and society, these innovations are expected to maximize the socio-economic impact of waqf for sustainable development. The research provides strategic insights into leveraging digital technology to optimize waqf potential in Indonesia.